2022
DOI: 10.1097/md.0000000000029693
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting factors associated with blood culture positivity: Critical factors after the introduction of automated continuous monitoring blood culture systems

Abstract: Blood culture is the main tool used to identify causative pathogens. Adequate volume and number of culture sets are considered key to blood culture positivity rate. It is not known whether these factors remain critical to the positivity rate after the introduction of automated continuous blood culture system monitoring.We measured blood volume per bottle and described the distribution of blood volume and number of culture sets. Multivariate logistic regression was performed to determine the independent associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…17 Investigations that had evaluated multiple human blood samples taken within a 24-h period found that the detection rate increased from 65.1–73.1% for the first blood samples to 80.4–89.7% and 95.7–98.2% for 2 and 3 blood cultures, respectively. 3,12,13 Our detection rate for 2 blood cultures was only 9.1%, which could be explained by a limited sample size ( n = 11), and 36.2% for 3 blood cultures ( n = 47). Although collecting multiple blood samples at 30–60-min intervals has been common practice, studies have demonstrated that multiple samples drawn (almost) simultaneously had similar detection rates, 2 which has been explained by a cumulatively higher amount of blood cultured per human patient.…”
mentioning
confidence: 74%
“…17 Investigations that had evaluated multiple human blood samples taken within a 24-h period found that the detection rate increased from 65.1–73.1% for the first blood samples to 80.4–89.7% and 95.7–98.2% for 2 and 3 blood cultures, respectively. 3,12,13 Our detection rate for 2 blood cultures was only 9.1%, which could be explained by a limited sample size ( n = 11), and 36.2% for 3 blood cultures ( n = 47). Although collecting multiple blood samples at 30–60-min intervals has been common practice, studies have demonstrated that multiple samples drawn (almost) simultaneously had similar detection rates, 2 which has been explained by a cumulatively higher amount of blood cultured per human patient.…”
mentioning
confidence: 74%
“…Tỷ lệ này của chúng tôi tương đồng với một số nghiên cứu khác trong và ngoài nước. Nghiên cứu của Pei-Chin Lin tại Đài Loan cho tỷ lệ cấy máu dương tính là 13,7% 9. Một nghiên cứu khác tại Trung Quốc cũng cho tỷ lệ cấy máu dương tính là…”
unclassified